Analisis determinan pendapatan petani kelapa sawit dengan produksi sebagai variabel intervening di Desa Suka Damai Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Novika, Arisca; Rahmadi, Selamet; Bhakti, Adi (Jurnal Paradigma Ekonomika, 2025)
This study aims to analyze the socio-economic characteristics, income generated by oil palm farmers and analyze factors that can directly and indirectly affect the income of oil palm farmers with production as an intervening variable in Suka Damai Village, Tebing Tinggi District, Tanjung Jabung Barat Regency. The types of data used in this study are primary data and secondary data. The method used in this research is path analysis. The results in this study indicate that the number of plants and fertilizers have a positive and significant effect on production while plant age and prices have no effect on oil palm production in Suka Damai Village. Fertilizer, price and production have an effect on income while plant age and number of plants have no effect on the income of oil palm farmers in Suka Damai Village. The results of path analysis show that there is an indirect relationship between the number of plants and fertilizer on income through production. While plant age and price do not indirectly have a significant effect on income through production.